A Review of Antifungal Resistance in West Africa - Muhindo, Abraham Bwalhuma; Aliero, Adamu Almustapha; Syalhasha, Festo Mwebaze; Ntulume, Ibrahim; Eilu, Emmanuel; Odoki, Martin; Mutebi, Joe (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Knowledge of local and regional antimicrobial resistance (AMR) is important for clinical decision-making. However, surveillance capacity for fungal infections let alone antifungal resistance is lacking throughout West Africa, and current antifungal resistance data are sparse. We sought to address this gap by summarizing all available high-quality data on antifungal resistance in West Africa. We searched the PubMed database, African Journals Online archives, and free web searches in October and December 2023 using the terms